IMPLICATIONS OF LITERACY KKN-T STUDENTS IN INCREASING PEOPLE'S INTEREST IN READING AND LITERACY BY UTILIZING TBM IN WILAGARA VILLAGE - Patmawati Patmawati; Hilmi Fajriansyah; Muhamad Raihan; Angga Wisnu Muhamad Raihan Octctora; Ahmad Rois Nur Fadilah; Salsabila Puspa Wangi; Ravly Evana Tri Handika; Shafa Indah P; Muhammad Rizky; Oktaviani Ramadhani; Adinda Fatimah; Irfan Khaerul Umam; Rivaldi Irfansyah; Nurdiyanto Nurdiyanto (Ann Publisher, 2026)
Background. Literacy is an important foundation for the progress of individuals and communities, but in many rural areas of Indonesia, including Wilanagara Village, reading interest and literacy levels are still low due to limited access to reading materials, facilities, and reading habits that are not optimal. The Literacy Thematic Community Service Program (KKN) is present as an innovative response to overcome this issue by utilizing the Community Reading Park (TBM) of Wilanagara Village as a center for non-formal learning activities. Purpose. The purpose of this service is to implement the role of KKN students as agents of change in increasing reading interest and literacy skills, as well as empowering TBM managers and the community to ensure the program. Method. Students carry out a series of program strategies, including assistance in the management of TBM (cataloging and labeling of books), interactive literacy training for children, and active collaboration with village officials and community leaders. Result. Despite challenges such as limited TBM facilities and inadequate management participation, the program has succeeded in increasing the active participation of the community (especially children) and building the foundation of a more organized TBM management system. Conclusion. This KKN program not only improves basic literacy in the short term but also creates an inclusive learning community and encourages a sustainable literacy culture. Implementation. This program is an effective model of community empowerment to improve the quality of human resources at the village level.